Optimal Linear Income Taxation and Education Subsidies under Skill-Biased Technical Change - Bas Jacobs; Uwe Thuemmel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies how linear tax and education policy should optimally respond to skill-biased technical change (SBTC). SBTC affects optimal taxes and subsidies by changing i) direct distributional benefits, ii) indirect redistributional effects due to wage-(de)compression, and iii) education distortions. Analytically, the effect of SBTC on these three components is shown to be ambiguous. Simulations for the US economy demonstrate that SBTC makes the tax system more progressive, since SBTC raises the direct distributional benefits of income taxes, which more than offset their larger indirect distributional losses, and it increases education distortions. Also, SBTC lowers optimal education subsidies, since SBTC generates larger direct distributional losses of education subsidies, which more than offset their larger indirect distributional gains, and it exacerbates education distortions.
Keywords: H20; H50; I20; J20; O30; 330; human capital; general equilibrium; optimal taxation; education subsidies; technological change